Multivariate analysis of knowledge, attitude, culture, and motivation factors towards premarital reproductive health to prevent stunting - Tri Sunarsih (Universitas Jenderal Achmad Yani Yogyakarta, 2026)
Background: Premarital reproductive health plays an important role in preparing for a healthy pregnancy; however, factors such as knowledge, attitude, culture, and motivation are often analyzed separately, resulting in a lack of comprehensive understanding.Objective: This study aimed to analyze the influence of knowledge, attitude, culture, and motivation on premarital reproductive health among prospective couples using a multivariate approach.Methods: This quantitative study used an analytical observational design with a cross-sectional approach conducted at Religious Affairs Offices (KUA) in Kulon Progo. A total of 260 respondents were selected using proportionate random sampling. Results: All independent variables were significant in the initial model (p<0.001). However, in the multivariate analysis, only knowledge showed a significant effect (p<0.001; OR=3.130). Attitude, culture, and motivation were not statistically significant (p>0.05), although they showed positive tendencies. The model explained 52.9% of the variance (Nagelkerke R²=0.529).Conclusion: Strengthening reproductive health education for prospective couples is essential to improve preconception readiness and support stunting prevention efforts.